Народні промисли та ремесла Поділля: історико-етнографічні дослідження краю ХІХ–ХХ ст. - Ющенко, О. (Народна творчість та етнографія, 2008)
It is possible to select three basic periods in research of folk trades and handicrafts of Podillya: 19th – the beginning of 20th centuries, 1920s – 1960s, and 1970s up to now. The first period is characterized by ponderable contribution of the foreign and Russian researchers to the development of поділлєзнавство, the second – by the development and becoming of Ukrainian ethnologic science. The third period is most fruitful in the research of the noted problem.